2018
DOI: 10.1007/s10103-018-2466-0
|View full text |Cite
|
Sign up to set email alerts
|

Can photobiomodulation associated with implantation of mesenchymal adipose-derived stem cells attenuate the expression of MMPs and decrease degradation of type II collagen in an experimental model of osteoarthritis?

Abstract: This study aimed to determine whether photobiomodulation therapy (PBMT) could improve the bioavailability and chondroprotective benefits of mesenchymal stem cells injected into the knees of rats used as an experimental model of osteoarthritis (OA) as well as reduce the expression of matrix metalloproteinases (MMPs) and degradation of type II collagen (COL2-1) in the cartilage. Adipose-derived stem/stromal cells (ADSCs) were collected from three male Fischer 344 rats and characterized by flow cytometry. Fifty f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 58 publications
1
32
0
Order By: Relevance
“…In this study, qPCR analysis revealed that IL-1β significantly upregulated IL-1β, IL-6, and TNF-α mRNA levels in NHAC-Kn cells and that these levels were significantly attenuated after irradiation of the IL-1β-stimulated chondrocytes with a high-frequency near-infrared diode laser at 4 or 8 J/cm 2 . The gene expression of IL-1β, IL-6, and TNF-α in rat models of acute joint inflammation [54,55] and in the cartilage of rat models of OA [56] decreased significantly after LLLT (808 nm, 142 J/cm 2 ) and laser irradiation (808 nm, 71 J/cm 2 ), respectively. Moreover, photobiomodulation therapy (830 nm, 214 J/cm 2 ) effectively reduced the OA-induced IL-1β, IL-6, and TNF-α protein expression in experimental rat OA models [57].…”
Section: Discussionmentioning
confidence: 98%
“…In this study, qPCR analysis revealed that IL-1β significantly upregulated IL-1β, IL-6, and TNF-α mRNA levels in NHAC-Kn cells and that these levels were significantly attenuated after irradiation of the IL-1β-stimulated chondrocytes with a high-frequency near-infrared diode laser at 4 or 8 J/cm 2 . The gene expression of IL-1β, IL-6, and TNF-α in rat models of acute joint inflammation [54,55] and in the cartilage of rat models of OA [56] decreased significantly after LLLT (808 nm, 142 J/cm 2 ) and laser irradiation (808 nm, 71 J/cm 2 ), respectively. Moreover, photobiomodulation therapy (830 nm, 214 J/cm 2 ) effectively reduced the OA-induced IL-1β, IL-6, and TNF-α protein expression in experimental rat OA models [57].…”
Section: Discussionmentioning
confidence: 98%
“…Sufficient collagen II is crucial for cartilage biomechanical properties ( 25 ), while previous findings determined that MMP-13 is the primary protein involved in cartilage degradation in the course of OA by cleaving collagen II ( 26 ). MMP-1 degrades type I, II, III, VII, X, IX and other types of collagen and aggrecan, while MMP-13 mainly cleaves collagen type II, IV and IX, osteonectin and perlecan in the cartilage ( 27 ). When stimulated by catabolism and anabolism, HA suppresses MMP-1 and MMP-13 ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Physical methods that have been studied include photobiomodulation and electromagnetic fields (EMFs). 69,70 In a rat model of OA, photobiomodulation performed daily for 7 days after cell delivery resulted in improved cell survival, collagen II, TIMP, and IL-10 expression, and decreased inflammatory gene and MMP expression. 52 Testing of EMFs was done in vitro and demonstrated an ability to improve differentiation under IL-1b treatment.…”
Section: Improving Cell Therapy In Musculoskeletal Environmentsmentioning
confidence: 99%